2020
DOI: 10.3390/jcm9113763
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of Pirfenidone in Idiopathic Pulmonary Fibrosis: Long-Term, Real-World Data from European IPF Registry (eurIPFreg)

Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is a chronic progressive fibrotic pulmonary disease with rising incidence. In this study the effectiveness of pirfenidone, as measured by longitudinal change in individual slope of forced vital capacity (FVC) prior to and after initiating pirfenidone treatment, was evaluated in IPF patients recruited into the European registry for idiopathic pulmonary fibrosis (eurIPFreg). Secondary variables were the evaluation of the change in individual slope of diffusion capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…Because IPF is a heterogeneous disease with a variable course, predicting disease outcomes is difficult. Indices of lung function at both baseline and functional decline in the progression of the disease have proved to have prognostic significance in IPF; that is, lower FVC and DLCO at baseline herald greater decline in lung function and poor prognosis (20,21). In accordance with that, our present study found that the baseline FVC and DLCO were lower in the non-survival group.…”
Section: Discussionsupporting
confidence: 88%
“…Because IPF is a heterogeneous disease with a variable course, predicting disease outcomes is difficult. Indices of lung function at both baseline and functional decline in the progression of the disease have proved to have prognostic significance in IPF; that is, lower FVC and DLCO at baseline herald greater decline in lung function and poor prognosis (20,21). In accordance with that, our present study found that the baseline FVC and DLCO were lower in the non-survival group.…”
Section: Discussionsupporting
confidence: 88%
“…Our cohort, together with other two PPF cohorts, didn't reach the media survival time with 4-year, 5-year and 7-year follow up respectively. In contrast, the media survival time of IPF is 3-5 years according to previous reports [14,20]. These data suggest that the change in FVC% was similar in patients with IPF and patients of PPF, but the overall survival of PPF was better than that of IPF.…”
Section: Discussionsupporting
confidence: 61%
“…The antifibrotic drug, pirfenidone, reduces lung function decline in patients with IPF compared with placebo [4,5] and is used in clinical practice [6,7]. In addition, several recent studies have reported that pirfenidone might reduce mortality in patients with IPF [8,9].…”
Section: Introductionmentioning
confidence: 99%